Constellation : Friedrich Nietzsche and Walter Benjamin in the now-time of history - McFarland, James, 1962- (Book collections on Project MUSE., 2012)
This title provides an extended exploration of the relationship between Walter Benjamin, the Weimar-era revolutionary cultural critic, and the radical philosopher Friedrich Nietzsche.